Estudo da recristalização dinâmica do aço inoxidável austenítico F 138, utilizado em próteses ortopédicas - Geronimo, Fabio Henrique Casarini (2009)
In order to analyze the microstructure and to know the dynamic softening mechanics that take place during the hot work in F 138 stainless steel, physical simulation was carried out through continuous isothermal hot torsion tests in a wide range of temperatures and strain rates, covering the real conditions of processing used in the manufacture of orthopedic implants with this material. The plastic flow stress curves obtained in this study showed a typical behavior of dynamic recrystallization. Also was determined the peak and steady-state stresses (σp, σss) and strains (εp, εss) and also the value of apparent activation energy for F 138 stainless steel, which is Q = 475kJ/mol. Through the curves of work-hardening rate vs. equivalent stress (θ vs. σ), the values of critical stress (σc) and strain (εc) for initiation of dynamic recrystallization are obtained. The metallographic observation was used to measure the average grain size under all deformation conditions, and also for the pre-deformed grain, D0 = 85.1μm. Thus it was possible to obtain empirical mathematical equations for the studied steel, which relate the processing parameters with the average grain size, since the resulting grain varies with processing conditions. The obtained data in this study will form a database which could be used in softwares of thermomechanical processing numerical simulation, which will permit the previous evaluation of resulting microstructure in a hot work processing of this material.